Interpretation Strategy and Awareness of the Counselor's Body Attitude in the Counseling Process - Indah Wijayanti; Mudjiran; Yeni Karneli (Journal Of Psychology, Counseling And Education, 2024)
The success of a counseling process is largely influenced by the competence of the counselor Confidentiality must be respected by the counselor during and after the counseling session. Without the consent of the counselee, a counselor is not allowed to disclose the results of the therapy session to a third party. A counselor has violated the code of ethics of the guidance and counseling profession if he/she does not maintain the confidentiality of information or conversations of the counselee during the counseling process. Moreover, this may jeopardize the counselor's job. Therefore, this study concentrates on body awareness and interpretation techniques as one of the counseling approaches for both individuals and groups.